Anti-Salmonella Activity of a Novel Peptide, KGGDLGLFEPTL, Derived from Egg Yolk Hydrolysate - Thippawan Pimchan; Fu Tian; Kanjana Thumanu; Sureelak Rodtong; Jirawat Yongsawatdigul (MDPI AG, 2023)
The present study aimed to characterize the mode of action of a novel antimicrobial peptide isolated from egg yolk hydrolysate. The EYHp6, KGGDLGLFEPTL, exhibited inhibition against Salmonella enterica serovar Typhimurium TISTR 292 and S. enterica serovar Enteritidis DMST 15679 with a MIC value of 2 mM. In contrast, S. enterica serovar Newport ATCC 6962 and other strains of Typhimurium and Enteritidis were inhibited at 4 mM. EYHp6 increased the cell membrane permeability of S. Typhimurium TISTR 292, leading to DNA leakage. Membrane integrity determined by propidium iodide and SYTO9 staining visualized by confocal microscopy demonstrated that EYHp6 at 1 × MIC induced disruption of cell membranes. Electron microscopy revealed that treatment of S. Typhimurium with EYHp6 led to damage to the cell membrane, causing the leakage of intracellular contents. Synchrotron-based Fourier-transform infrared spectroscopy indicated that EYHp6 killed S. Typhimurium by targeting fatty acids and nucleic acids in the cell membrane. The peptide did not show hemolytic activity up to 4 mM. These findings suggest that EYHp6 could be a promising antibacterial agent for controlling the growth of S. enterica.